Analisis Penerapan Internet Of Things (IoT) dalam Pertanian Cerdas di Era 4.0 - Nida Rahma Lestari; Reza Ramdan Permana; Yehezkiel Tampanatu Rotty; Harry Pribadi Fitrian (Fakultas Teknik Universitas Hamzanwadi, 2026)
The development of Internet of Things (IoT) technology has had a major impact on various fields, including agriculture. This technology enables monitoring, control, and decision-making processes to be carried out automatically using sensors and systems connected to a network. This study aims to analyze the application of IoT technology in smart agriculture in Indonesia and globally using the Narrative Literature Review method. The method used was to review 17 nationally accredited (SINTA 3-5) and international journals published between 2019 and 2025. The results showed that the application of IoT in agriculture focused on monitoring soil moisture, air temperature, automatic irrigation control, and monitoring the quality of the plant environment. The application of Internet of Things (IoT) technology in agriculture has been proven to increase resource utilization efficiency, crop productivity, and work process effectiveness. In addition, one of the studies reviewed reported that the application of an IoT-based fertilization system was able to reduce fertilizer use by up to 49% for certain commodities. However, there are still several challenges, such as high implementation costs, network infrastructure conditions, data security issues, and farmers' limited technological knowledge. In conclusion, the application of IoT in agriculture has great potential to support digital transformation in Indonesia's agricultural sector towards a more sustainable and efficient agricultural system.